The Effect of Drug Prohibition on Drug Prices: Evidence from the Markets for Cocaine and Heroin - Miron, Jeffrey A. (The Review of Economics and Statistics, 2003)
This paper examines the effect of drug prohibition on the black market prices of cocaine and heroin. The paper examines the ratio of retail to farmgate price for cocaine, heroin, and several legal goods, and it compares legal versus black market prices for cocaine and heroin. The results suggest that cocaine and heroin are substantially more expensive than they would be in a legalized market, but to a lesser degree than suggested in previous research.